Perceived Effectiveness on the Use of English Language in Teaching Mathematics and Science - HUSARIDA HUSARIDA; ROLANDO DOLLETE (Indonesian Research Journal in Education |IRJE|, 2019)
This study investigated the perceived level of effectiveness on the use of English in teaching mathematics and science in one bilingual school in Jambi, Sumatra, Indonesia. Students from grades 5 and 6 and six teachers participated in the study by providing data on their experiences in learning and teaching Mathematics and Science using English medium for instruction. A questionnaire was used in this study consisting of the socio-demographic characteristics of the students and teacher, school factors, perceived level of effectiveness on the use of English in teaching mathematics and science. Statistical procedures of descriptive statistics and Pearson correlation using SPSS 20 were used to analyze data. The major findings of the study were (1) most participants perceived that English medium instruction helped them in improving their English reading and writing skills; (2) most participants agreed with the helpfulness of English as a Medium Instruction; (3) there was no significant relationship between teachers’ socio-demographic characteristics and the perceived level of effectiveness on the use of English in teaching Mathematics and Science; (4) there was a significant relationship between students’ socio-demographic characteristics and the perceived level of effectiveness on the use of English in teaching mathematics and science; (5) there was a significant relationship between school factors such as facilities and equipment with the perceived level of effectiveness on the use of English in teaching mathematics and sciences perceived by students; (6) there was a negative significant relationship between school factors and the perceived level of effectiveness on the use of English in teaching mathematics and science perceived by teachers. Recommendations are also discussed.